Studies of charging mechanisms in impurity-helium condensates by means of impedance spectroscopy and current spectroscopy - Pelmenev, A.A.; Bykhalo, I.B.; Krushinskaya, I.N.; Boltnev, R.E. (Физика низких температур, 2019)
A new simple experimental technique has been elaborated to test applicability of impedance spectroscopy for studying processes during destruction of impurity-helium condensates. Combination of methods of optical spectroscopy, impedance spectroscopy and current spectroscopy to study the destruction processes of impurityhelium condensates has been applied for the first time. Experimental data have demonstrated a rather good sensitivity of the technique and proved formation of charged clusters during a destruction stage of impurity-helium condensates. Просту експериментальну методику розроблено та успішно випробувано для використання можливостей спектроскопії імпедансу при дослідженні процесів на стадії руйнування зразків домішково-гелієвих конденсатів. Вперше використано комбінацію методів спектроскопії імпедансу, струмової спектроскопії та оптичної спектроскопії для дослідження руйнування домішково-гелієвих конденсатів. Отримані результати показали високу чутливість нової методики та підтвердили появу зарядів (заряджених нанокластерів) на стадії руйнування домішково-гелієвих конденсатів. Ключові слова: нанокластери, домі Простая экспериментальная методика разработана и успешно опробована для использования возможностей спектроскопии импеданса при исследовании процессов на стадии разрушения образцов примесь-гелиевых конденсатов. Впервые использована комбинация методов спектроскопии импеданса, токовой спектроскопии и оптической спектроскопии для исследования разрушения примесь-гелиевых конденсатов. Полученные результаты показали высокую чувствительность новой методики и подтвердили появление зарядов (заряженных нанокластеров) на стадии разрушения примесьгелиевых конденсатов.